2013
DOI: 10.1371/journal.pone.0075076
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the Intermolecular Recognition Mechanism between Keap1 and IKKβ Combining Homology Modelling, Protein-Protein Docking, Molecular Dynamics Simulations and Virtual Alanine Mutation

Abstract: Degradation of certain proteins through the ubiquitin-proteasome pathway is a common strategy taken by the key modulators responsible for stress responses. Kelch-like ECH-associated protein-1(Keap1), a substrate adaptor component of the Cullin3 (Cul3)-based ubiquitin E3 ligase complex, mediates the ubiquitination of two key modulators, NF-E2-related factor 2 (Nrf2) and IκB kinase β (IKKβ), which are involved in the redox control of gene transcription. However, compared to the Keap1-Nrf2 protein-protein interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 67 publications
(66 reference statements)
1
34
0
Order By: Relevance
“…These studies showed that Keap1 regulated TNF-induced NF-κB activity via IKKβ. The E(T/S)GE motif, which is found only in the IKKβ subunit of the IKK complex, was essential for direct interaction with the C-terminal Kelch domain of Keap1 (27,41). However, we show evidence that the entire IKK complex, along with its homolog TBK1, is significantly affected by Keap1, even though only IKKβ seemed to be ubiquitinated and possibly degraded through Keap1.…”
Section: Discussionmentioning
confidence: 55%
“…These studies showed that Keap1 regulated TNF-induced NF-κB activity via IKKβ. The E(T/S)GE motif, which is found only in the IKKβ subunit of the IKK complex, was essential for direct interaction with the C-terminal Kelch domain of Keap1 (27,41). However, we show evidence that the entire IKK complex, along with its homolog TBK1, is significantly affected by Keap1, even though only IKKβ seemed to be ubiquitinated and possibly degraded through Keap1.…”
Section: Discussionmentioning
confidence: 55%
“…These results are sustained by the presence of a NF-B binding site in the Nrf2 gene (42) (Fig. 8B) and by the fact that IK-␤ (IB␣ kinase) contains an ETGE motif that enables it to bind to KEAP1 (43,44). Also, NRF2 deficiency results in increased ROS levels, which induce IB␣ phosphorylation and subsequent degradation, increasing p65-NF-B levels and NF-B proinflammatory processes (Fig.…”
Section: Discussionmentioning
confidence: 93%
“…Phosphoglycerate mutase 5 (PGAM5) may also be degraded in a Keap1-dependent fashion [282], as may inhibitor of κB kinase β (IKKβ) [283, 284]. In the former case, PGAM5, a serine–threonine phosphatase known to activate ASK1 [285], contains a conserved N-terminal ESGE motif, which binds to Keap1 in a manner similar to that of the Nrf2 ETGE motif.…”
Section: Molecular Regulation Of Nrf2mentioning
confidence: 99%